A systematic review of medicinal plants used against Echinococcus granulosus - Ali, Rehman (PLoS One, 2020)
Cystic echinococcosis (CE) is a zoonotic helminthiasis caused by different species of the genus Echinococcus, and is a major economic and public health concern worldwide. Synthetic anthelmintics are most commonly used to control CE, however, prolonged use of these drugs may result in many adverse effects. This study aims to discuss the in vitro/in vivo scolicidal efficacy of different medicinal plants and their components used against Echinococcus granulosus. Google Scholar, ScienceDirect, PubMed and Scopus were used to retrieve the published literature from 2000–2020. A total of 62 published articles met the eligibility criteria and were reviewed. A total of 52 plant species belonging to 22 families have been reported to be evaluated as scolicidal agents against E. granulosus worldwide. Most extensively used medicinal plants against E. granulosus belong to the family Lamiaceae (25.0%) followed by Apiaceae (11.3%). Among various plant parts, leaves (36.0%) were most commonly used. Essential oils of Zataria multiflora and Ferula asafetida at a concentration of 0.02, and 0.06 mg/ml showed 100% in vitro scolicidal activity after 10 min post application, respectively. Z. multiflora also depicted high in vivo efficacy by decreasing weight and size while also causing extensive damage to the germinal layer of the cysts. Plant-based compounds like berberine, thymol, and thymoquinone have shown high efficacy against E. granulosus. These plant species and compounds could be potentially used for the development of an effective drug against E. granulosus, if further investigated for in vivo efficacy, toxicity, and mechanism of drug action in future research.